Final answer:
The first 6 elements of the given sequences are provided, along with their recursive definitions.
Step-by-step explanation:
For the sequence given by (a) an = -3n - 10, the first 6 elements are:
a1 = -13, a2 = -16, a3 = -19, a4 = -22, a5 = -25, a6 = -28
The recursive definition for this sequence is:
a1 = -13
an = an-1 - 3, for n > 1
For the sequence given by (b) an = (1+(-1)^n)^n, the first 6 elements are:
a1 = 0, a2 = 4, a3 = 0, a4 = 16, a5 = 0, a6 = 64
The recursive definition for this sequence is:
a1 = 0
an = (1+(-1)^n)^n, for n > 1
For the sequence given by (c) an = 2n!(2), the first 6 elements are:
a1 = 4, a2 = 16, a3 = 48, a4 = 128, a5 = 320, a6 = 768
The recursive definition for this sequence is:
a1 = 4
an = 2n!(2), for n > 1